Prospects for hormonal contraception in patients with breast diseases: the Mona Lisa smile effect. A review - Mekan R. Orazov; Viktor E. Radzinskiy; Evgeny D. Dolgov (IP Berlin A.V., 2023)
Breast diseases (BD) are among the most urgent issues of modern reproductive medicine. This organ is an integral part of the female reproductive system and undergoes cyclic changes during the menstrual cycle. The modern "nosological trio" of BD is mastodynia, benign dysplasia, and breast cancer. These diseases have an extremely high prevalence, and breast cancer, in turn, ranks 1st in the structure of mortality from malignant neoplasms of the female reproductive system. All these aspects warrant the research of the key pathogenetic mechanisms of these conditions. However, one of the most relevant topics in modern gynecology is the counseling on the selection of contraceptive methods in these patients. Therefore, it is necessary to address the safety of hormonal contraceptive methods and to analyze innovations in hormonal contraceptives, which may have several protective and risk-reducing properties for BD.